2009
DOI: 10.1093/hmg/ddp557
|View full text |Cite
|
Sign up to set email alerts
|

Relative tissue expression of homologous torsinB correlates with the neuronal specific importance of DYT1 dystonia-associated torsinA

Abstract: A three base-pair deletion in the widely expressed TOR1A gene causes the childhood onset, neurological disease of DYT1 dystonia. Mouse Tor1a gene knockout also specifically affects the developing nervous system. However, in both cases, the basis of neuronal tissue specificity is unknown. TorsinA is one of four predicted mammalian torsin ATPases associated with assorted cellular activities (AAA+) proteins, raising the possibility that expression of a functionally homologous torsin compensates for torsinA loss i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
126
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(141 citation statements)
references
References 47 publications
11
126
1
Order By: Relevance
“…Next, we confirmed the previous observation of a second TorA isoform in liver extracts (37,38). Based on our observation that this isoform co-migrates with TorAp on SDS-PAGE gels (Fig.…”
Section: -Nitroisatin Is a Cell-permeable Inhibitor Useful For Intersupporting
confidence: 91%
See 2 more Smart Citations
“…Next, we confirmed the previous observation of a second TorA isoform in liver extracts (37,38). Based on our observation that this isoform co-migrates with TorAp on SDS-PAGE gels (Fig.…”
Section: -Nitroisatin Is a Cell-permeable Inhibitor Useful For Intersupporting
confidence: 91%
“…Of note, TorAp has an electrophoretic behavior indistinguishable from the TorA isoforms in liver (Fig. 7C) (37,38), again suggesting in vivo relevance of our observations. Because potent inducers of ER stress (with the exception of DTT) do not induce Torsin processing (Figs.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The torsin family is comprised of four torsin genes in mammals consisting of torsinA, torsinB, torsin2, and torsin3, with several orthologs found in metazoans including zebrafish, C. elegans and D. melanogaster [65][66][67]. Sequence alignment revealed that all four mammalian torsin proteins contain an endoplasmic reticulum (ER) signal sequence and AAA+ domain and are localized to the ER lumen and nuclear envelope (NE) [67].…”
Section: A Dyt1: Early-onset Torsion Dystoniamentioning
confidence: 99%
“…The torsin family is comprised of four torsin genes in mammals consisting of torsinA, torsinB, torsin2, and torsin3, with several orthologs found in metazoans including zebrafish, C. elegans and D. melanogaster [65][66][67]. Sequence alignment revealed that all four mammalian torsin proteins contain an endoplasmic reticulum (ER) signal sequence and AAA+ domain and are localized to the ER lumen and nuclear envelope (NE) [67]. Although torsinB may be functionally similar, only torsinA exhibits high expression in neurons throughout the mammalian brain with subcellular localization extending from the ER and NE, to the cytoplasm and neuronal processes; this is suggestive of a neuronal specificity for torsinA expression that corresponds with its significance in EOTD [67][68][69].…”
Section: A Dyt1: Early-onset Torsion Dystoniamentioning
confidence: 99%